2012
DOI: 10.1037/a0026586
|View full text |Cite
|
Sign up to set email alerts
|

Recursive partitioning analysis of lifetime suicidal behaviors in Asian Americans.

Abstract: Previous studies have shown that multiple factors predict suicidal behavior in Asian Americans but have provided little guidance on how to rate the relative impact of these risks. To increase our understanding of suicide in Asian Americans, recursive partitioning analysis was used to identify risk factors most relevant to predicting suicidal behaviors and enhance the decision-making process of clinicians faced with clients presenting with multiple risk factors. Using a classification and regression tree (CART)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
3
22
1
Order By: Relevance
“…Our results also highlighted specific aspects of psychopathology that were uniquely associated with a history of NSSI in Asian students, including obsessive–compulsive symptoms, experiential avoidance, and poor relationships with peers and parents. This is consistent with previous studies suggesting that interpersonal problems differentiate Chinese adolescents with a history of NSSI from those with no such history (You et al., ), and with research suggesting that interpersonal stressors are related to self‐damaging behavior more broadly in Asian populations (Kuroki & Tilley, ; Wong & Maffini, ; Wong et al., ). Further, previous research has highlighted an association between anxiety symptoms and NSSI in minority students (Chesin et al., ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results also highlighted specific aspects of psychopathology that were uniquely associated with a history of NSSI in Asian students, including obsessive–compulsive symptoms, experiential avoidance, and poor relationships with peers and parents. This is consistent with previous studies suggesting that interpersonal problems differentiate Chinese adolescents with a history of NSSI from those with no such history (You et al., ), and with research suggesting that interpersonal stressors are related to self‐damaging behavior more broadly in Asian populations (Kuroki & Tilley, ; Wong & Maffini, ; Wong et al., ). Further, previous research has highlighted an association between anxiety symptoms and NSSI in minority students (Chesin et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…Further, collective cultural values may increase the relevance of interpersonal context for NSSI in Asian populations. Consistent with this possibility, previous research shows that poor family relationships are an important precipitant of suicidal behavior in Asians (Kuroki & Tilley, ; Wong & Maffini, ; Wong, Uhm, & Li, ). Together, this suggests that Asian students who engage in NSSI, particularly those who are highly oriented to traditional Asian cultural values, may differ from their Caucasian counterparts with respect to the prevalence and frequency of NSSI, and with respect to their likelihood of seeking mental health services.…”
mentioning
confidence: 54%
“…Given Chinese cultural values of patriarchy and familial solidarity, suicide may be viewed as an acceptable or even honorable option for Chinese individuals who believe they have shamed or burdened their family (Qin & Mortensen, ). Numerous other research studies have also shown that suicidal ideation and attempts are associated with dysfunctional family dynamics, parent–child conflict, or lack of family cohesion among various Asian American youth, adolescent, and adult samples (e.g., Cheng et al., ; Kim & Kim, ; Kuroki & Tilly, ; Lau, Jernewall, Zane, & Myers, ).…”
Section: Suicide Risk Factors Versus Subtypesmentioning
confidence: 96%
“…When it is deficient, people may experience suicidal thoughts. Especially, family cohesion and family conflict have been identified as important predictors of suicide [5,11]. In addition, the single household family might induce suicidal ideation because they may lack social connectedness [12].…”
Section: Introductionmentioning
confidence: 99%